2021
DOI: 10.1111/joss.12684
|View full text |Cite
|
Sign up to set email alerts
|

Comparing classical descriptive analysis with modified descriptive analysis, modified rate‐all‐that‐apply, and modified check‐all‐that‐apply

Abstract: There have been ongoing attempts to create new rapid sensory methods that allow one to have similar outcomes to conventional descriptive analysis but with less training and time. Check-all-that-apply and rate-all-that-apply methods seem to work very well when relatively large numbers of consumers are involved and with relatively more considerable differences among the samples in a product set. In this study, results from well-trained descriptive analysis panels were compared to those obtained by using a modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…A total of 12 assessors (8 women and 4 men) aged between 22 and 44 years (mean age: 30 ± 8 years) were selected from students and employees of the Department of Food, Environmental and Nutritional Sciences of the University of Milan. The number of assessors involved is in line with that of previous studies [ 20 , 27 ]. Only subjects ≥ 18 years of age who were regular wine consumers (wine consumption corresponding to 1–2 glasses per week) were involved in the study.…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…A total of 12 assessors (8 women and 4 men) aged between 22 and 44 years (mean age: 30 ± 8 years) were selected from students and employees of the Department of Food, Environmental and Nutritional Sciences of the University of Milan. The number of assessors involved is in line with that of previous studies [ 20 , 27 ]. Only subjects ≥ 18 years of age who were regular wine consumers (wine consumption corresponding to 1–2 glasses per week) were involved in the study.…”
Section: Methodssupporting
confidence: 54%
“…This is especially true for winemakers who often belong to very small enterprise realities. Examples of the successful application of the RATA method with a reduced number of trained or semi-trained assessors are available for cream soups [ 27 ], milk powders [ 26 ] and chocolate [ 20 ], but not for wine.…”
Section: Introductionmentioning
confidence: 99%
“…For the sensory analysis of Chardonnay and Sauvignon Blanc wines, three phases (defining the sensory attributes, rapid training, and RATA test) each consisting of one round table, two training sessions (1 h each), and two MRATA sessions (modified rate all that apply [ 24 ]) were performed. Cysensy–an SQL binding sensory analysis web software developed in collaboration with the Computer Science faculty of the Free University of Bozen/Bolzano was used during the training and MRATA sessions.…”
Section: Methodsmentioning
confidence: 99%
“…The SN and RATA used in this study have been utilised as sensory profiling methods to substitute for conventional DA. Several studies have already identified methodological validity with high RV coefficients by similar product configurations as DA (Dehlholm et al ., 2012; Oppermann et al ., 2017; Oliver et al ., 2018; Nishida et al ., 2021). The results of this study demonstrated that the HMFA map obtained from the SN result (Fig.…”
Section: Discussionmentioning
confidence: 99%